Effects of aircraft noise on annoyance, sleep disorders, and blood pressure among adult residents near the Orio al Serio International Airport (BGY), Italy - Carugno, Michele; Imbrogno, Pietro; Zucchi, Alberto; Ciampichini, Roberta; Tereanu, Carmen; Sampietro, Giuseppe; Barbaglio, Giorgio; Pesenti, Bruno; Barretta, Francesco; Bertazzi, Pier Alberto; Pesatori, Angela Cecilia; Consonni, Dario (La Medicina del Lavoro, 2018)
Background: Aircraft noise may cause several non-auditory health effects, including annoyance, sleep disorders, hypertension, cardiovascular diseases, and impaired cognitive skills in children. Objectives: To perform a cross-sectional study among adult residents near the Orio al Serio International Airport (BGY), Italy to investigate the association between aircraft noise, annoyance, sleep disorders, blood pressure levels, and prevalence of hypertension. Methods: Residential addresses of subjects aged 45-70 years were geocoded and classified in three groups according to noise levels: <60 (Reference), 60-65 (Zone A), and 65-75 dBA (Zone B). A sample of subjects was invited to undergo a personal interview and blood pressure measurements. Multiple linear and robust Poisson regression models were used to analyze quantitative and categorical variables, respectively. Results: Between June and September 2013, we enrolled 400 subjects (166 in the Reference Zone, 164 in Zone A, and 70 in Zone B). Compared to the Reference Zone, we found elevated adjusted annoyance scores (day and night) in Zone A (+2.7) and Zone B (+4.0) (p<0.001) and about doubled proportions of severely annoyed subjects (p<0.001). Reported sleep disorders in the previous month were also more frequent in Zones A and B. Sleep disorders in general were 19.9% in the Reference Zone, 29.9% in Zone A, and 35.7% in Zone B (p<0.001). Conclusions: We found a strong association between aircraft noise levels, annoyance, and sleep disorders among adult residents near the Orio al Serio International Airport. We found no relationship with blood pressure levels and prevalence of hypertension.